2017
DOI: 10.1186/s12985-017-0828-z
|View full text |Cite
|
Sign up to set email alerts
|

New insights into HCV replication in original cells from Aedes mosquitoes

Abstract: BackgroundThe existing literature about HCV association with, and replication in mosquitoes is extremely poor. To fill this gap, we performed cellular investigations aimed at exploring (i) the capacity of HCV E1E2 glycoproteins to bind on Aedes mosquito cells and (ii) the ability of HCV serum particles (HCVsp) to replicate in these cell lines.MethodsFirst, we used purified E1E2 expressing baculovirus-derived HCV pseudo particles (bacHCVpp) so we could investigate their association with mosquito cell lines from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Hepatitis virus has been found to be stable and viable for at least 1 month in the gut of bed bugs ( Cymex lectularius and C. hemipterus ) and R. prolixus , with the virus being detected in feces and transmitted trans stadially (Blow et al, 2001 ; Silverman et al, 2001 ). Besides that, Hepatitis virus has been detected in mosquitoes in endemic areas, and it has been found that Hepatitis virus efficiently replicates in cultures of mosquito cells (Fallecker et al, 2017 ). The possibility of Hepatitis transmission by arthopods has been hindered by the ignorance of natural reservoirs of the virus or documentation of prevalence of the virus in putative vectors (Houldsworth, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis virus has been found to be stable and viable for at least 1 month in the gut of bed bugs ( Cymex lectularius and C. hemipterus ) and R. prolixus , with the virus being detected in feces and transmitted trans stadially (Blow et al, 2001 ; Silverman et al, 2001 ). Besides that, Hepatitis virus has been detected in mosquitoes in endemic areas, and it has been found that Hepatitis virus efficiently replicates in cultures of mosquito cells (Fallecker et al, 2017 ). The possibility of Hepatitis transmission by arthopods has been hindered by the ignorance of natural reservoirs of the virus or documentation of prevalence of the virus in putative vectors (Houldsworth, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mosquito is the most profound vector of disease in the world . While several flaviviruses such as dengue and Zika are transmitted to humans by the Aedes mosquito, hepatitis C virus is a human flavivirus with no arthropod vector. , The factors that distinguish viruses capable of being vectored by insects as well as the capacity for viruses to gain this ability have not been fully elucidated and remain unclear. In summary, we have shown that the expression of human NPC1 protein in Aedes cells alone is not sufficient to permit filovirus infection, indicating at the presence of multiple blocks to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many significant arboviruses, including Yellow Fever virus, West Nile virus, dengue virus, and Zika virus, belong to the family Flaviviridae and are vectored by mosquitoes belonging to the genus Aedes . However, certain other members of the Flaviviridae family, such as hepatitis C virus, with similar genomes and structures to these arboviruses, are not vectored by the mosquito. , The molecular mechanisms responsible for this distinction within the Flaviviridae family are unknown but bring up the questions of what factors may be necessary for a virus to be vectored by an arthropod and which viruses could potentially gain this ability, especially among closely related viruses.…”
mentioning
confidence: 99%
“…MultiBac is successfully used for a range of applications beyond producing protein complexes for structural and mechanistic studies. For example, customized MultiBac baculoviral genomes were prepared to express virus-like 15 particles (VLPs), which are promising vaccine candidates as they resemble live viruses but do not contain genetic material and are thus safe [22,39]. Here, an influenza VLP is shown in a schematic drawing and in an electron micrograph [22] (centre, top).…”
Section: Broadening the Scope: Multibac Moves To Emblmentioning
confidence: 99%